2004
DOI: 10.1103/physrevlett.93.017001
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Phase in Lightly DopedLa2xSrxC

Abstract: In the low doping range of x from 0.01 to 0.06 in La2−xSrxCuO4, a narrow electron paramagnetic resonance (EPR) line has been investigated. This line is distinct from the known broad line, both due to probing Mn 2+ ions. The narrow line is ascribed to metallic regions in the material, and its intensity increases exponentially upon cooling below ∼ 150 K. The activation energy deduced ∆ = 460(50) K is nearly the same as that found in the doped superconducting regime by Raman and neutron scattering. The intensity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…[24]) that the local charge carrier concentration in CuO 2 planes can be influenced by isotope mass change of the in-plane oxygen ions due to the microscopic electronic phase separation into metallic and dielectric regions in the CuO 2 plane. The results of the EPR study of such a phase separation in lightly doped La 2−x Sr x CuO 4 showed that the starting point for the creation of metallic regions is a formation of a bipolaron by two three-spin-polarons (3SP) via exchange by phonons [25,26]. EPR experiments demonstrated that by cooling, bipolarons condense into metallic clusters or stripes similar to the process described in the previous Section.…”
Section: Planar Oxygen Isotope Effects Related To Charge Heterogeneitymentioning
confidence: 71%
See 1 more Smart Citation
“…[24]) that the local charge carrier concentration in CuO 2 planes can be influenced by isotope mass change of the in-plane oxygen ions due to the microscopic electronic phase separation into metallic and dielectric regions in the CuO 2 plane. The results of the EPR study of such a phase separation in lightly doped La 2−x Sr x CuO 4 showed that the starting point for the creation of metallic regions is a formation of a bipolaron by two three-spin-polarons (3SP) via exchange by phonons [25,26]. EPR experiments demonstrated that by cooling, bipolarons condense into metallic clusters or stripes similar to the process described in the previous Section.…”
Section: Planar Oxygen Isotope Effects Related To Charge Heterogeneitymentioning
confidence: 71%
“…The broad line disappears at y = 0.4 which can be related to the delocalization of the electronic holes in the stripes. The CuO 2 planes experience the electronic phase separation into metal and dielectric regions which were detected earlier by the EPR study [25]. The phase transition of underdoped cuprates into the superconducting state is accompanied by a strong planar isotope effect on the critical temperature T c what can indicate an important role of electron-phonon interactions in a formation of bipolarons and the metal regions in the CuO 2 planes.…”
Section: Planar Oxygen Isotope Effects Related To Charge Heterogeneitymentioning
confidence: 94%
“…Such a behavior was actually observed in these experiments. The microscopic electronic phase separation into metallic and dielectric regions in the CuO 2 planes was observed previously by the EPR method in lightly doped La 2Àx Sr x CuO 4 also in a metallic state [34]. It was proposed then that the starting point for the creation of metallic regions is a formation of a bipolaron by two three-spin-polarons with an assistance of phonons [35].…”
Section: Spin Dynamics and A Phase Separation In Superconducting Cuprmentioning
confidence: 94%
“…[6][7][8][9][10][11][12] The stripe order has also been observed by x-ray scattering. [12][13][14][15][16][17] Furthermore, an electron paramagnetic resonance study showed that micro-scopic electronic phase separation occurs in La 2−x Sr x Cu 0.98 Mn 0.02 O 4 with 0.01 ≤ x ≤ 0.06, 18 and a Cu nuclear magnetic resonance (NMR) study suggested that a large charge droplet ('blob') is formed in the electron-doped Nd 1.85 Ce 0.15 CuO 4−δ . 19 Much theoretical works has also been performed to study the behavior of the doped carriers in HTSC.…”
Section: Introductionmentioning
confidence: 99%